Analisis Fungsi Pendengaran pada Masinis PT Kereta Api Indonesia (Persero): Kajian Tingkat Kebisingan Lokomotif - Sangadi, Fitri Juniasih; Ratrikaningtyas, Prima Dhewi (J-Mestahat, 2024)
Long-distance trains are generally a series of passenger cars pulled by diesel-electric locomotives. With a fairly high level of locomotive noise, the driver is susceptible to noise exposure. The study aims to determine the relationship between length of service and hearing function of all drivers, assistant drivers, driver supervisors and prospective drivers of PT. Kereta Api Indonesia, and its relationship with locomotive cabin noise. Primary data were taken from the audiometry results during the 2023 medical check-up and service period data using an electronic questionnaire. The noise of the CC206 locomotive when driving ranged from 75 dBA to 120.9 dBA. The audiometry analysis data and service period have c2count = 117.23, so it is concluded that there is a relationship between service period and decreased hearing function. This can happen because the longer the driver is exposed to noise, the higher the risk of hearing loss. The application of additional soundproofing, installation of air conditioning units and adjustment of the flute position in the locomotive can be done to reduce noise in the locomotive cabin.